2016
DOI: 10.3147/jsfp.51.125
|View full text |Cite
|
Sign up to set email alerts
|

Antiparasitic Effect of Formalin, Trichlorfon, Hydrogen Peroxide, and Copper Sulfate on the Parasitic Isopod <i>Caecognathia coralliophila</i>

Abstract: Caecognathia coralliophila is known as a pathogenic ectoparasite infecting tiger grouper Epinephelus fuscoguttatus in a hatchery in Sabah, Malaysia. The effects of copper sulfate, formalin, trichlorfon, and hydrogen peroxide on the survival of C. coralliophila larvae were tested in vitro. The larvae were exposed to different concentrations of each chemical for 10, 20, 30, 60 min, or 24 h. Trichlorfon was found to be the most effective, killing the parasites within 24 h at 0.2 ppm. Consequently, the toxicity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…In this study, the e cacy of trichlorfon varied from 20 to 23%. Contrary to what was observed in this study with acanthocephalan, Thing et al (2016) found that trichlorfon killed isopod parasites Caecognathia coralliophila within 24 hours at 0.2 mg/L in farmed tiger grouper Epinephelus fuscoguttatus. Regarding withdrawal period, the analyzes of the muscle of grass carp Ctenopharingodon idella revealed that after ve days of the last administration of 0.25 mg/L of tricloforn, no signs of bioaccumulation of the chemical or of its metabolites were found (Guimarães et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, the e cacy of trichlorfon varied from 20 to 23%. Contrary to what was observed in this study with acanthocephalan, Thing et al (2016) found that trichlorfon killed isopod parasites Caecognathia coralliophila within 24 hours at 0.2 mg/L in farmed tiger grouper Epinephelus fuscoguttatus. Regarding withdrawal period, the analyzes of the muscle of grass carp Ctenopharingodon idella revealed that after ve days of the last administration of 0.25 mg/L of tricloforn, no signs of bioaccumulation of the chemical or of its metabolites were found (Guimarães et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, for the comparison of the anti-parasitic effect of the plant extracts, we used formalin as a positive control, since it is vastly utilized for the removal of parasites in aquaculture facilities 14 . Besides, other chemicals such as trichlorfon, hydrogen peroxide and copper sulfate have also been used as an anti-parasitic agent 32 . In Malaysia, other drugs like benzalkonium chloride, acriflavine, malachite green, hypochlorite and poly-vinyl pyrrolidine are also utilized for the removal of parasites in aquaculture facilities 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Formalin has also been used to treat another type of fish parasite. For example, Thing et al [34] demonstrated that exposure to 100 and 200 ppm formalin killed pathogenic isopods, Caecognathia coralliophila, in vitro within 24 h. In the antiparasitic test, 250 and 400 ppm of formalin were also found to be effective to remove Benedenia seriolae and Zeuxapta seriolae monogeneans from the yellowtail kingfish, Seriola lalandi [35]. In addition, the antiparasitic effectiveness of formalin in the freshwater environment to control the protozoan parasite Ichthyophthirius multifiliis had also been reported [36].…”
Section: Discussionmentioning
confidence: 99%